NHS Scotland Public Benefit and Privacy Panel (PBPP) – Much Ado about Governance 3 years on - Morris, Carole; Gray, Ashley; Scott, Jennifer (International Journal of Population Data Science, 2018)
Introduction Since its’ inception in May 2015, the Public Benefit and Privacy Panel has provided a centralised, simplified and truly national Information Governance scrutiny process. It has successfully harnessed expertise across NHS Scotland health boards implementing a collaborative approach which contributes to consistency and continued capacity development across the sector. Objectives and Approach Over the last 3 years PBPP developed several procedures within its’ operations to become more efficient and achieve consistent decision making to ensure there is adequate information sharing amongst both Tier 1 and Tier 2 PBPP members. These components include: Integrated working with eDRIS team to support applicants pre submission Established an operational group with action plan Monthly reporting to NHS Boards Information Governance colleagues Annual learning and sharing workshop Annual audit of Tier 1 Proportionate Governance approved applications Documented Case Law Information Sheets on categories of applications to aid consistent decision making Results Tier 1 panel members have noted that the quality of applications is noticeably improved when assistance is provided pre-submission aiding the speed of their proportionate review and that reference documents provide valuable information on the foundations of previous decisions. As a result of this and other improvements 90% of all applications are approved by Tier 1. Only those deemed highly complex or novel proposals are usually referred to Tier 2 at which 8% are reviewed and approved out of committee via email and the remaining 2% are heard at a Full Committee meeting. Whilst the average “clocked” days for an application is approximately 31 days. Conclusion/Implications PBPP needs to continue to evolve in order to continue providing efficient and pragmatic IG assessments for new technologies, more complex, voluminous data linkages and innovation. This is no mean feat in a fast paced environment and we have to ensure those involved are given sufficient time to do so.